Interactive Design Psychology and Artificial Intelligence-Based Innovative Exploration of Anglo-American Traumatic Narrative Literature - Hou, Xia; Omar, Noritah; Wang, Jue (Frontiers in Psychology, 2022)
The advent of the intelligence age has injected new elements into the development of literature. The synergic modification of Anglo-American (AAL) Traumatic Narrative (TN) literature by Artificial Intelligence (AI) technology and Interactive Design (ID) psychology will produce new possibilities in literary creation. Firstly, by studying Natural Language Processing (NLP) technology, this paper proposes a modification Language Model (LM) based on the double-layer Recurrent Neural Network (RNN) algorithm and constructs an intelligent language modification system based on the improved LM model. The results show that the performance of the proposed model is excellent; only about 30% of the respondents like AAL literature; the lack of common cultural background, appreciation difficulties, and language barriers have become the main reasons for the decline of reading willingness of AAL literature. Finally, AI technology and ID psychology are used to modify a famous TN work respectively and synergically, and the modified work is appreciated by respondents to collect their comments. The results corroborate that 62% of the respondents like original articles, but their likability scores have decreased for individually modified work by AI or ID psychology. By comparison, under the synergic modification efforts of AI and ID psychology, the popularity of the modified work has increased slightly, with 65% of the respondents showing a likability to read. Therefore, it is concluded that literary modification by single ID psychology or AI technology will reduce the reading threshold by trading off the literary value of the original work. The core of literary creation depends on human intelligence, and AI might still not be able to generate high-standard literary works independently because human minds and thoughts cannot be controlled and predicted by machines. The research results will provide new ideas and improvement directions for the field of AI-assisted writing.